Global Professional Service Firms and the Challenge of Institutional Complexity: 'Field Relocation' as a Response Strategy. (24th February 2015) - Faulconbridge, James; Muzio, Daniel
ABSTRACT: In this paper we use the case of the internationalization of English law firms into Italy, and the refocusing of their operations on the city of Milan, to make a number of contributions to existing literatures on responses to institutional complexity. First, we contribute to the literature on how organizations address complexity at the field level, by revealing the role of 'field relocation' as a particular response strategy. We also identify a number of organizational tactics – re‐scoping, re‐scaling, and re‐staffing – through which 'field relocation' is accomplished. Second, we also show the importance of further developing our understanding of the geography of institutional fields by highlighting how the 'receptivity' of different field locations may affect responses to complexity. This identifies the importance of geographically locating fields and sub‐fields in studies of organizational responses to institutional complexity.